Radio Pirenaica: The Oral Historical Memory of the Grimau Case - de la Quintana García, Alfonso (Documentación de las Ciencias de la Información, 2022)
The Grimau case consisted of the arrest, conviction and execution of one of the most important communist leaders in the fight against Franco´s regime infiltrated in Spain in 1962, and its corresponding judicial process full of very serious irregularities, including an alleged suicide attempt. This news would not have had an international impact if it had not been for Radio España Independiente (REI), known by public opinion as La Pirenaica, a clandestine station subsidized by the Soviet Union. The methodology used has been to use the Historical Archives of the Communist Party of Spain, the script section of Radio España Independiente, from November 7, 1962, the day Julián Grimau was arrested, until April 20, 1963, when he was executed. A total of 164 days of consulted broadcasts. The most important conclusions are: To emphasize that, despite the serious irregularities of the judicial process and the strong impact of its execution on world public opinion, this case has not been part of the current awareness of Spanish public opinion.